2001
DOI: 10.1021/jp004374q
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Computational Thermochemistry:  Isomerization of Sulfine and Its Enthalpy of Formation

Abstract: Density functional (DFT), second-order perturbation theory (MP2), and coupled-cluster [(CCSD(T)] calculations using Pople's basis sets up to 6-311++G(3df,2pd) and Dunning's correlation consistent basis sets have been employed to determine the enthalpy of formation of sulfine, CH2SO, 1, using the isodesmic reaction CH2S + SO2 ⇌ CH2SO + SO. Previous calculations showed an inconsistency between the enthalpy of formation obtained using this methodology, Δf H o 298.15(1) = −52 ± 10 kJ/mol, and the value obtained em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…The DFT results were also confirmed with calculations carried out with the CCSD(T) method, and finally, the values obtained at the B3PW91/ 6-311þþG(3df,2pd) and FC-CCSD(T)/6-311þþG(2df,2pd) levels of theory were averaged and accepted as Δ f H 298 °(CH 2 SO). In their second paper, 124 the previously calculated value of 52.0 ( 10.0 kJ/mol was confirmed on the basis of DFT, MP2, and CCSD(T) calculations with Dunning's correlation-consistent basis sets. In order to solve the discrepancy between Ruttink and associates' CBS-QB3 120 and their previous results, 123,124 Ventura and co-workers 125 performed DFT calculations on three additional reaction schemes not considered earlier.…”
Section: Articlementioning
confidence: 66%
See 1 more Smart Citation
“…The DFT results were also confirmed with calculations carried out with the CCSD(T) method, and finally, the values obtained at the B3PW91/ 6-311þþG(3df,2pd) and FC-CCSD(T)/6-311þþG(2df,2pd) levels of theory were averaged and accepted as Δ f H 298 °(CH 2 SO). In their second paper, 124 the previously calculated value of 52.0 ( 10.0 kJ/mol was confirmed on the basis of DFT, MP2, and CCSD(T) calculations with Dunning's correlation-consistent basis sets. In order to solve the discrepancy between Ruttink and associates' CBS-QB3 120 and their previous results, 123,124 Ventura and co-workers 125 performed DFT calculations on three additional reaction schemes not considered earlier.…”
Section: Articlementioning
confidence: 66%
“…In their second paper, 124 the previously calculated value of 52.0 ( 10.0 kJ/mol was confirmed on the basis of DFT, MP2, and CCSD(T) calculations with Dunning's correlation-consistent basis sets. In order to solve the discrepancy between Ruttink and associates' CBS-QB3 120 and their previous results, 123,124 Ventura and co-workers 125 performed DFT calculations on three additional reaction schemes not considered earlier. They concluded that the discrepancy is connected to the presence of the triplet SO in the isodesmic reaction (see above) used to calculate the heat of formation of sulfine.…”
Section: Articlementioning
confidence: 66%
“…The method of isodesmic reactions, in which the number of each kind of formal bond is conserved, has been employed very successfully to calculate HOF from total energies obtained from ab initio calculations . In order not to break the skeleton, we take CL‐20 and pyridine as a reference compound; the isodesmic reaction (1) used to derive the HOF of PNTNPHATCD is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Hence, various reports of the heats of formation of the molecules have been given by various isodesmic reaction schemes [15,[30][31][32][33][34]. Ventura et al [35,36] have pointed out that DFT methods using modest basis sets and isodesmic reactions can produce very accurate thermochemical information, in many cases superior to results from Gaussian-2 (G2) and even the coupled cluster method (CCSD(T)).…”
Section: Introductionmentioning
confidence: 99%